Garlic Extract: Inhibition of Biochemical and Biophysical Changes in Glycated HSA - Mohd W. A. Khan (MDPI AG, 2021)
Glycation of various biomolecules contributes to structural changes and formation of several high molecular weight fluorescent and non-fluorescent, advanced glycation end products (AGEs). AGEs and glycation are involved in various health complications. Synthetic medicines, including metformin, have several adverse effects. Natural products and their derivatives are used in the treatment of various diseases due to their significant therapeutic qualities. Allium sativum (garlic) is used in traditional medicines because of its antioxidant, anti-inflammatory, and anti-diabetic properties. This study aimed to determine the anti-glycating and AGEs inhibitory activities of garlic. Biochemical and biophysical analyses were performed for in vitro incubated human serum albumin (HSA) with 0.05 M of glucose for 1, 5, and 10 weeks. Anti-glycating and AGEs inhibitory effect of garlic was investigated in glycated samples. Increased biochemical and biophysical changes were observed in glycated HSA incubated for 10 weeks (G-HSA-10W) as compared to native HSA (N-HSA) as well as glycated HSA incubated for 1 (G-HSA-1W) and 5 weeks (G-HSA-5W). Garlic extract with a concentration of ≥6.25 µg/mL exhibited significant inhibition in biophysical and biochemical changes of G-HSA-10W. Our findings demonstrated that garlic extract has the ability to inhibit biochemical and biophysical changes in HSA that occurred due to glycation. Thus, garlic extract can be used against glycation and AGE-related health complications linked with chronic diseases in diabetic patients due to its broad therapeutic potential.